In silico and in vivo evaluation of the anti-cryptosporidial activity of eugenol - Gattan, Hattan S.; Wakid, Majed H.; Qahwaji, Rowaid M.; Altwaim, Sarah; Mahjoub, Haifaa A.; Alfaifi, Mashael S.; Elshazly, Hayam; Al-Megrin, Wafa Abdullah I.; Alshehri, Eman Abdullah; Elshabrawy, Hatem A.; El-kady, Asmaa M. (Frontiers in Veterinary Science, 2024)
Abstract: Background: Cryptosporidiosis is an opportunistic parasitic disease widely distributed worldwide. Although Cryptosporidium sp. causes asymptomatic infection in healthy people, it may lead to severe illness in immunocompromised individuals. Limited effective therapeutic alternatives are available against cryptosporidiosis in this category of patients. So, there is an urgent need for therapeutic alternatives for cryptosporidiosis. Recently, the potential uses of Eugenol (EUG) have been considered a promising novel treatment for bacterial and parasitic infections. Consequently, it is suggested to investigate the effect of EUG as an option for the treatment of cryptosporidiosis. Materials and methods: The in silico bioinformatics analysis was used to predict and determine the binding affinities and intermolecular interactions of EUG and Nitazoxanide (NTZ) toward several Cryptosporidium Parvum (C. parvum) lowa II target proteins. For animal study, five groups of immunosuppressed Swiss albino mice (10 mice each) were used. Group I was left uninfected (control), and four groups were infected with 1000 oocysts of Cryptosporidium sp. The first infected group was left untreated. The remaining three infected groups received NTZ, EUG, and EUG + NTZ respectively on the 6th day post-infection (dpi). All mice were sacrificed 30 dpi. The efficacy of the used formulas was assessed by counting the number of C. parvum oocysts excreted in stool of infected mice, histopathological examination of the ileum and liver tissues and determination of the expression of iNOS in the ileum of mice in different animal groups. Results: treatment with EUG resulted in a significant reduction in the number of oocysts secreted in stool when compared to infected untreated mice. In addition, oocyst excretion was significantly reduced in mice recived a combination therapy of EUG and NTZ when compared with those received NTZ alone. EUG succeeded in reverting the histopathological alterations induced by Cryptosporidium infection either alone or in combination with NTZ. Moreover, mice received EUG showed marked reduction of the expression of iNOS in ilieal tissues. Conclusion: Based on the results, the present study signified a basis for utilizing EUG as an affordable, safe, and alternative therapy combined with NTZ in the management of cryptosporidiosis.